How to help older adults learn new technology? Results from a multiple case research interviewing the internet technology instructors at the senior learning center. (February 2019) - Chiu, Ching-Ju; Tasi, Wan-Chen; Yang, Wan-Lin; Guo, Jong-Long
Abstract: The incorporation of technology into everyday life has become the core of the learning process of older adults. However, how technology is implemented in senior learning environments is not well known. This study employed a multiple case research method focused on understanding employment, adjustment, and revision of the teaching strategies used by experienced instructors at senior learning centers. The results indicate that the instructors developed different teaching strategies when teaching older learners, which included: 1) Reserved teaching: where instructors reserve some of the learning content, so elderly learners can continue their learning of a topic if they continue to participate in the same class; 2) Unscripted performance: where instructors flexibly adjust or jump outside the box of the previously scheduled teaching content to respond to ever-changing learning situations and the needs of the elderly learners, and 3) Assistance from peers: where instructors can ease the one-to-many teaching burden and also strengthen the learning confidence of the elderly. Highlights: Elderly learn technology requires different education pedagogy. Reserved teaching can create a familiar but fresh feeling for elder learners. Unscripted teaching cope with ever-changing learning situations for elderly learners. Create a little helper from the elderly learners is critical in elderly teaching.